FAKTOR PENGHAMBAT PEMBELAJARAN TAHFIDZ AL QUR’AN PADA SISWA SD/MI - Ali, Hasna; Budianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify and analyze the main obstacles in the Qur’anic memorization (tahfidz) learning process at the elementary school or Islamic elementary school level in Indonesia. The phenomenon explored concerns the gap between memorization targets and the actual effectiveness of tahfidz implementation at the primary education level. A qualitative approach based on library research with a phenomenological design was employed to explore the meanings and contextual challenges reflected in scholarly literature from 2020 to 2025. Data sources consisted of peer-reviewed journal articles, academic proceedings, and official government documents selected purposively. Data analysis followed a thematic method based on the interactive model by Miles, Huberman, and Saldaña. The findings reveal two interrelated categories of obstacles: (1) internal factors, such as low student motivation, limited ability in recitation due to underdeveloped phonetic and cognitive skills, and weak short-term memory; and (2) external factors, including the lack of interactive digital media, an overloaded academic curriculum, insufficient teacher training, and minimal parental involvement. These findings indicate that the success of tahfidz learning does not solely depend on memorization techniques but requires an integrated support system involving education policies, teacher preparedness, and family engagement. This study contributes theoretically to the development of a tahfidz learning model grounded in psychological needs and educational technology, and offers practical implications for curriculum development, teacher training, and strategies to enhance family involvement. Future research is recommended to empirically explore students’ and teachers’ experiences through field-based qualitative methods.